2015
DOI: 10.1039/c4bm00365a
|View full text |Cite
|
Sign up to set email alerts
|

Tumor extracellular acidity activated “off–on” release of bortezomib from a biocompatible dendrimer

Abstract: A nanoparticle with a specific response to tumor extracellular acidity provides a new option in the design of tumor-targeted delivery systems. In this study, we report such a pH-responsive polymer which realizes an "off-on" release of bortezomib in tumor acidic microenvironments. A dendrimer surface is grafted with a neutral shell to reduce its cellular uptake, and its interior is functionalized with catechol moieties. An anticancer drug, bortezomib, is loaded within the dendrimer interior via a boronate-catec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…Compared with PBA, boric acid polymers are more often used to construct reversible-covalent borate ester bonds. Bortezomib (BTZ) is an effective and specific proteasome inhibitor for cancer treatment (Wang et al, 2015 ). Su et al ( 2011 ) coupled BTZ with a polymer carrier containing catechol through a reversible dynamic covalent borate ester bond and then synthesized a new type of cell-targeted and pH-sensitive polymer carrier by modifying biotin-targeted ligands that are selectively ingested by cancer cells through the mechanism mediated by cell surface receptors, thus delivering the anticancer drug BTZ to cancer cells.…”
Section: Development Of Ta Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with PBA, boric acid polymers are more often used to construct reversible-covalent borate ester bonds. Bortezomib (BTZ) is an effective and specific proteasome inhibitor for cancer treatment (Wang et al, 2015 ). Su et al ( 2011 ) coupled BTZ with a polymer carrier containing catechol through a reversible dynamic covalent borate ester bond and then synthesized a new type of cell-targeted and pH-sensitive polymer carrier by modifying biotin-targeted ligands that are selectively ingested by cancer cells through the mechanism mediated by cell surface receptors, thus delivering the anticancer drug BTZ to cancer cells.…”
Section: Development Of Ta Self-assemblymentioning
confidence: 99%
“…However, the activity of BTZ against solid tumors is lower; systemic use will lead to a higher risk of adverse reactions, and BTZ resistance has been observed. Wang et al ( 2015 ) reported a pH-responsive polymer based on a polyamide dendrimer, which is functionalized by the catechol group inside the dendrimer and achieves the “off-on” release of BTZ in the slightly acidic tumor microenvironment through catechol–borate dynamic covalent bonding interactions with BTZ, allowing the therapeutic effect of BTZ in cancer treatment to be maintained while reducing its adverse reactions. Recently, in view of the factors that limit the clinical application of BTZ, such as low water solubility, instability, a non-specific distribution, and poor permeability to tumors, Zhao et al ( 2019a ) designed a new strategy without any organic synthesis and modification.…”
Section: Development Of Ta Self-assemblymentioning
confidence: 99%
“…pH-sensitivity pH-responsive manner of polymeric nanoparticles and BTZ as novel strategy, can be considered to be a promising method for optimizing loading and control release of this drug. Boronic acid group in BTZ is mainly responsible for the reaction with other moieties such as hydroxyl 27 or carbonyl 29 interactions with BTZ is high at low pH, so they choose potassium phosphate buffer at pH 6.0 as an optimum medium for obtaining best loading efficiency by providing a balance between osmotic and ionic characteristics of chitosan. 7 Sensitivity to pH is also an important factor in BTZ release in tumor microenvironment with acidic pH.…”
Section: Multifunctionalizationmentioning
confidence: 99%
“…Thus, photosensitizers for PDT should be little or no harm under light-free conditions, such as pormer sodium (Photofrin), 16 Visudyne and Foscan, which have been approved by the U.S. Food and Drug Administration (FDA). 11,17 As one of the most promising nanocarriers, dendritic macromolecules have been employed for cancer therapy, including dendritic polyesters, [18][19][20] poly(propylene imine), 21,22 polyamidoamine (PAMAM), [23][24][25][26] triazine dendrimers, 27,28 peptide dendrimers, [29][30][31][32] and dendritic polyglycerols (dPGs), 33,34 which are a class of macromolecules with a highly branched three-dimensional architecture, multi-functionalities, and potential applications in biomedicine, especially for drug delivery. These dendrimers as drug carriers could allow for the delivery of a higher drug loading content (DLC) and drug loading efficiency (DLE) with reduced cytotoxic side effect.…”
Section: Introductionmentioning
confidence: 99%